The Correlation of Physical Activity and Stress Level with Blood Pressure during Pregnancy - Jamaluddin, Sarah Nur Azizah; Andi Irhamnia Sakinah; Fhirastika Annisha Helvian; Sari Ifdiana Jalal; Muhsin Mahfudz, (Alami Journal (Alauddin Islamic Medical) Journal, 2025)
Hypertension during pregnancy is a serious condition that may lead to complications for both the mother and fetus. This condition is associated with various risk factors, including physical inactivity and psychological stress. This study aims to determine the relationship between physical activity and stress levels with blood pressure of pregnant women. This quantitative study with a cross-sectional design involved 143 pregnant women, who were surveyed using the Pregnancy Physical Activity Questionnaire (PPAQ) to assess physical activity and the Pregnancy Stress Rating Scale (PSRS) to assess stress levels. The research finding showed that the majority of pregnant women engaged in heavy physical activity (69.2%) had mild stress levels (74.1%). Spearman's rho test results indicated a significant relationship between physical activity (p<0.05) and stress (p<0.05) with blood pressure of pregnant women, with correlation strengths of R=0.524 and R=-0.353, respectively. There is a relationship between physical activity and stress of pregnant women with their blood pressure